Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams Poverty and Its Sources Among 100 workers the causes of poverty were : 1899 Old age, illness [Picture] Large family [Picture] Low wages [Picture] Unemployment [Picture] Others [Picture] Each symbol represents 1% of all workers The symbols on a background are the workers living in poverty The causes of poverty are indicated by additional symbols and words 15X/2/566/303